Regarding the lack of transparency in technical documents for the treatment of patients with COVID-19 in Peru - Taype-Rondan, Alvaro (2020)
The Peruvian Ministry of Health (MINSA, in Spanish) has published ministerial resolutions (MR) with the aim of regulating the treatment of people affected by COVID-19. These MR include the use of specific drugs for COVID-19, such as tocilizumab, corticosteroids, enoxaparin, hydroxychloroquine, and ivermectin. These guidelines do not make clear what process was followed to make decisions, how each of these decisions was justified, who their authors are or their potential conflicts of interest. It is important to make an effort to promptly make these data transparent, especially in a subject in which there is still not much evidence, such as COVID-19. In this article, we present controversies on the use of specific drugs for COVID-19 established by MINSA, as well as recommendations on the decision-making process.